Penerapan Cutomer Relationship Management (CRM) Dengan Menggunakan Metode Analytic Network Process (ANP) Pada Perusahaan Ritel - Nofiyati, Nofiyati; Sediyono, Eko; Nurhayati, Oky Dwi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2013)
Retail industry or retail business is a fast-growing business in the midst of global competition conditions. One strategy to attract more consumers are Customer Relationship Management (CRM). The successful implementation of CRM in the enterprise is influenced by several environmental perspectives, strategies, customers and products / services, processes, participants, infrastructure, and information technology are integrated in the framework of Work System (WS). This research was carried out by applying the method of Multiple Criteria Decision Making (MCDM) that is able to accommodate the outer and inner linkage from multiple nodes / indicators are considered, namely the Analytical Network Process (ANP) to rank the quality of implementation CRM in retail companies and strong influential node / indicator of the best retail among three alternative the consisting of Alfamart, Indomaret and Smesco mart. From the results of application ANP method, obtained the rank quality of implementation CRM in retail companies with first rank is Indomaret the value of 1.0000; and the second is Alfamart with a value 0.9575; and the third is Smesco mart with a value of 0.8034. While node / indicator strong influence on the the best retail is level of chaos, long and short term planning, customer service, system integration, appropriate skills, technical infrastructure, easily of use and accessibility of information. Â  Keywords: Ritel, Customer Relationship Management (CRM), Analytic Network Process (ANP), Kerangka Work System (WS).